The potential and practice of arboreal camera trapping. Issue 10 (29th July 2021) - Moore, Jennifer F.; Soanes, Kylie; Balbuena, Diego; Beirne, Christopher; Bowler, Mark; Carrasco‐Rueda, Farah; Cheyne, Susan M.; Coutant, Opale; Forget, Pierre‐Michel; Haysom, Jessica K.; Houlihan, Peter R.; Olson, Erik R.; et al.
Abstract: Arboreal camera trapping is a burgeoning method providing a novel and effective technique to answer research questions across a variety of ecosystems, and it has the capacity to improve our understanding of a wide range of taxa. However, while terrestrial camera trapping has received much attention, there is little guidance for dealing with the unique challenges of working in the arboreal realm. Our review draws on the expertise of researchers from six continents and the broader literature to investigate the advantages and disadvantages of arboreal camera trapping, and challenges to consider when using this technology. We also include mini‐guides with detailed information on the current arboreal camera trap literature, mounts used to install arboreal cameras, tree climbing pointers and safety tips, methods for deploying cameras without climbing, and tips for managing interference with camera function. We find that arboreal camera traps have been most commonly used in the study of mammals in forests; however, there is potential for this method to be applied to a broad range of habitats including urban areas, and taxa such as birds, amphibians, invertebrates, and plants. Methods in arboreal camera trapping could be improved by developing a greater understanding of the factors affecting detection of species. The most common challenges of arboreal camera trapping are camera placement and camera site access. These can be overcome by understanding correct camera orientation, managing potential sources of interference in front of cameras, utilizing appropriate cameras mounts and training researchers properly. Given the benefits and opportunities presented by arboreal camera trapping, it is likely to become an ever‐more popular method of studying arboreal species and systems. The information synthesized in this review provides guidance for future studies to help direct more reliable and robust ecological inferences from arboreal camera trapping. Resumen: El fototrampeo arbóreo es un método emergente que brinda una técnica nueva y efectiva para responder a preguntas de investigación en una variedad de ecosistemas, y tiene la capacidad de mejorar nuestra compresión de una amplia gama de taxones. Sin embargo, mientras el fototrampeo terrestre ha recibido mucha atención, existen pocas pautas sobre cómo lidiar con los retos únicos de trabajar con cámaras en el ámbito arbóreo. Nuestra revisión se basa en la experiencia de investigadores de seis continentes y en la literatura en general para evaluar las ventajas y desventajas del fototrampeo arbóreo y los retos a considerar al utilizar esta tecnología. También incluimos mini‐guías con información detallada sobre la literatura actual acerca del uso de cámaras trampa en los árboles, soportes utilizados para colocar las cámaras trampa, indicaciones y consejos para trepar árboles y acceder al dosel de manera segura, métodos para colocar las cámaras sin trepar y consejos para el manejo de interferencia en el funcionamiento de la cámara. Nuestro estudio concluye que el fototrampeo arbóreo ha sido mayormente utilizado para el estudio de mamíferos en bosques. Sin embargo, esta metodología tiene el potencial de ser utilizada en un amplio rango de hábitats, incluyendo áreas urbanas, y taxones como aves, anfibios, invertebrados y plantas. Los métodos de fototrampeo arbóreo pueden mejorarse con una mayor comprensión de los factores que afectan la detección de especies. Los retos más comunes en el fototrampeo arbóreo son el acceso al sitio en el dosel donde se ubicará la cámara y la instalación de la misma. Estos retos se pueden superar entendiendo cuál es el mejor ángulo de orientación de la cámara, el manejo de las posibles fuentes de interferencia que se ubiquen delante de las cámaras, utilizando soportes apropiados para las cámaras y entrenando adecuadamente a los investigadores. Dados los beneficios y las oportunidades presentados por el fototrampeo arbóreo, es probable que se convierta en un método cada vez más popular para estudiar especies y sistemas arbóreos. La información sintetizada en esta revisión proporciona una guía que ayudará a futuros estudios a realizar inferencias ecológicas más confiables y sólidas en base al fototrampeo arbóreo. Résumé: Le piégeage photographique dans la couronne des arbres est une méthode en plein essor qui offre une technique novatrice et efficace pour répondre à des questions de recherche pour une variété d'écosystèmes, et permet d'améliorer notre compréhension d'une large diversité de taxons. Cependant, alors que le piégeage photographique au sol a reçu une grande attention, il y a peu de manuel pour répondre aux défis que posent les études dans le domaine de la canopée. Notre analyse repose sur l'expertise de chercheurs provenant de six continents et sur la littérature générale pour étudier les avantages et désavantages du piégeage photographique en canopée, mais aussi les défis à prendre en compte quand cette technologie est utilisée. Nous intégrons des mini‐guides contenant des informations détaillées de la littérature actuelle sur les pièges photographiques et les supports utilisés en canopée, des conseils pour grimper en toute sécurité aux arbres, les méthodes pour déployer ces appareils sans grimper et des conseils pour limiter les interférences lors de leur fonctionnement. Nous trouvons que les pièges photographiques en canopée ont été plus souvent utilisés pour étudier les mammifères dans les forêts, cette méthode ayant cependant un potentiel pour un large éventail d'habitats y compris les zones urbaines, et de taxons tels que les oiseaux, les amphibiens, les invertébrés, et les plantes. Les méthodes de piégeage photographique en canopée pourraient être optimisées en améliorant notre compréhension des facteurs qui affectent la détection des espèces. Les défis les plus courants du piégeage photographique sont le placement et l'accès au site de fixation des appareils. Ces problèmes peuvent être surmontés en identifiant les orientations les plus adaptées pour les appareils, en limitant les sources potentielles d'interférences devant les objectifs, en utilisant des supports appropriés ainsi qu'en formant correctement les chercheurs. Compte tenu des bénéfices et des opportunités que représente l'usage du piégeage photographique en canopée, cette méthode est de plus en plus utilisée pour étudier les espèces dans la canopée. Les informations synthétisées dans cette revue fournissent des indications pour les études futures afin de permettre des déductions écologiques plus fiables et plus solides à partir du piégeage photographique dans la couronne des arbres. Resumo: As armadilhas fotográficas em dossel arbóreo é um método emergente que fornece uma técnica nova e eficaz para responder a perguntas científicas em diversos ecossistemas e tem a capacidade de melhorar nossa compreensão de uma ampla gama de taxa . No entanto, embora o uso das armadilhas fotográficas terrestres tenha recebido muita atenção, existem poucas diretrizes sobre como lidar com os desafios exclusivos de trabalhar com câmeras em um ambiente arbóreo. Nossa revisão baseia‐se na experiência de pesquisadores de seis continentes e na literatura geral para avaliar as vantagens e desvantagens das armadilhas fotográficas em árvores e os desafios a serem considerados ao usar essa tecnologia. Também incluímos mini‐guias com informações detalhadas sobre a literatura atual sobre o uso de armadilhas fotográficas, suportes usados para sua instalação, indicações e dicas para subir em árvores e acessar o dossel com segurança, métodos para colocar câmeras sem escalar e dicas para manejo de interferências na operação da câmera. Nosso estudo conclui que as armadilhas fotográficas em dosseis arbóreos têm sido utilizadas principalmente para o estudo de mamíferos em florestas. No entanto, essa metodologia tem potencial para ser usada em uma ampla gama de habitats, incluindo áreas urbanas, e taxa como aves, anfíbios, invertebrados e plantas. Os métodos podem ser aprimorados com uma maior compreensão dos fatores que afetam a detecção de espécies. Os desafios mais comuns no uso das armadilhas fotográficas em árvores são o acesso ao local onde a câmera estará localizada no dossel, e a prórpia instalação destas câmeras. Esses desafios podem ser superados compreendendo o melhor ângulo de orientação da câmera, gerenciando fontes potenciais de interferência na frente das câmeras, usando suportes de câmera apropriados e treinando adequadamente os pesquisadores. Dados os benefícios e oportunidades apresentados pelo uso das armadilhas fotográficas em árvores, é provável que se torne um método cada vez mais popular de estudar espécies e sistemas arbóreos. As informações sintetizadas nesta revisão fornecem orientações que ajudarão estudos futuros a fazer inferências ecológicas mais confiáveis e robustas com base no uso desta técnica. 摘要: 作为一种新兴的技术方法, 树栖红外相机为我们探究多种生态系统中的科学问题提供了有效的技术支持, 可以进一步加深我们对广大生物类群的理解。然而, 相比广泛应用的地面相机监测技术, 我们依旧缺乏对于解决树栖红外相机应用相关问题的指导方针。 通过综述来自六大洲研究人员的专业技术知识和广泛的文献, 我们分析了树栖红外相机的优缺点及其实际应用中所面临的问题和挑战。同时基于现有文献信息, 我们撰写了树栖红外相机使用的迷你指南, 包括安装和固定相机的装置、爬树技巧和安全提示、无需攀爬部署相机的方法和解决干扰使相机正常工作的技巧。 结果发现树栖红外相机经常用于森林哺乳动物的研究, 但这种方法仍有其他潜在的应用, 如可应用于城市地区等的各种动物栖息地, 可应用于包括鸟类、两栖动物、无脊椎动物和植物等多种生物类群。通过进一步了解影响物种检测率的因素, 可以改进关于树栖红外相机的研究方法。树栖红外相机应用中最常见的挑战是相机的布置和相机位点的访问。这些问题可以通过确定正确的相机方向、处理相机镜头前的潜在干扰因素、使用合适的安装和固定装置及培训当地的研究人员来解决。 鉴于树栖红外相机的优点和所带来的机遇, 它很可能会成为研究树栖物种和生态系统更流行的技术方法。这篇综述提供的各种信息为未来相关研究提供了指导, 将有助于从树栖红外相机研究中获得更可靠和稳健的生态推论。